The Influence of Return on Equity, Environmental Risk Management and Stock Performance on Corporate Sustainability Performance - Tarigan, Josua; Valerie, Veronica (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
This study aims to determine the relationship between a firm's financial and environmental performance and the quality of the resulting corporate sustainability report. The analysis is conducted on 36 Indonesian listed firms in three sectors: primary industry and chemicals, mining, and consumer goods. Pooled Ordinary Least Square (OLS) model is used to identify the strength of the relationship between the independent and dependent variables. The results show that, with firm age and size serving as the control variables, Return on Equity, Stock Performance, and Environmental Risk Management considerably positively affect a firm's Corporate Sustainability Performance (CSP). According to the findings, the independent variables ROE, environmental risk management, and stock performance impact the firm's corporate sustainability performance quality, which is significant over the long run. Therefore, businesses should consider improving CSP quality as a strategic investment and maintain a solid rapport with stakeholders. By examining how a firm's financial performance and environmental risk management affect the quality of CSP, this study contributes to the CSP field. Keywords: corporate sustainability performance, environmental risk management, natural resources, return on equity, stock performance